A REVIEW OF CONSEQUENCES OF CONSUMER REGRET IN CYBER MARKETING - Saif Ali Jasim; Abbas Fadel Sultan; Sahar Jabbar Rahman (Journal Park Publishing, 2024)
The current research aims to study the opinions of previous literature towards the effects of the consequences of customer regret on cyber marketing, and this is what attracted the attention of many researchers and practitioners recently, because of the negative behavior of the customer of negative effects on the value of the organization and incurring significant material losses in addition to other effects that damage the reputation and image of the organization, and it is interesting that the retention of newly acquired customers, It is crucial because it is much less than the cost of gaining new customers, which means that the fate of the large amounts spent by organizations in order to build a sustainable relationship with the customer is unknown if the management of organizations does not strive to build solid standards that enable them to determine the correct methods of cyber marketing, especially since marketing budgets occupy a large part of the general budgets of organizations. As a result of the nature of the services that distinguish them from the goods, they require frequent interactions between the service provider and the customer, the psychological and emotional climate, in addition to the physical climate, is an essential criterion for the customer's assessment of the level of quality of services and the critical link of the customer's relationship with the service provider or organization.
Keywords: customer regret, cyber marketing.